Curricula for Teaching Students with Autism Spectrum Disorder - Chiang, Hsu-Min, editor (Cham : Springer International Publishing, 2017)
This book provides an extensive overview of curricula and instructional strategies for teaching children with autism spectrum disorder (ASD). It offers an empirically solid framework for designing and developing interventions for learners along the autism spectrum by reducing skill deficits and enhancing learner strengths while being flexible enough to allow for individual differences. The book discusses key concepts in educating individuals with ASD as they impact the processes of syllabus building, from planning goals and objectives to generating content choosing appropriate teaching strategies, and assessing progress. Chapters detail curriculum designs in academic areas such as language skills, science, and social studies, as well as functional skills, including independent living, career development, and preventing social victimization. The book concludes with recommendations for future interventions and curricula-building. Among the topics covered: Communication and autism spectrum disorder, Mathematical problem-solving instruction for students with ASD, Visual arts curriculum for students with ASD, How to build programs focused on daily living and adult independence, Sexuality education for students with ASD